Factors that promote the use of evidence-based knowledge among physiotherapists in the municipal health services: An interview study - Tove Bergan; Einar Egenberg; Nina Rydland Olsen (Fysioterapeuten, 2023)
Aim: The purpose of the study was to explore factors that promote the use of evidence-based knowledge among municipal physiotherapists.